2006
DOI: 10.1017/s146114570600719x
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the therapeutic response to risperidone and the dopamine D2 receptor polymorphism in Chinese schizophrenia patients

Abstract: Antipsychotic drugs exert both therapeutic and adverse effects through dopamine D2 receptor (DRD2) antagonism. Genetic variants of this receptor may be responsible for individual variations in neuroleptic response and may therefore be useful in predicting response. In this study we evaluated the role of six polymorphisms of the DRD2 gene in 125 risperidone-treated Chinese schizophrenia patients following the hypothesis that variation in the DRD2 gene could affect drug response. Response was categorized as a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 34 publications
3
54
0
2
Order By: Relevance
“…While they found no association between rs1799978 of DRD2 and schizophrenia, similar to our present result, this SNP has been given particular attention recently for its relationship to the phenotype of a differential treatment response within a patient group with schizophrenia (Lencz et al, 2006;Xing et al, 2007), suggesting the possibility of an association between this SNP and sub-phenotypes of schizophrenia.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While they found no association between rs1799978 of DRD2 and schizophrenia, similar to our present result, this SNP has been given particular attention recently for its relationship to the phenotype of a differential treatment response within a patient group with schizophrenia (Lencz et al, 2006;Xing et al, 2007), suggesting the possibility of an association between this SNP and sub-phenotypes of schizophrenia.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the negative association results at Stage 2 in our analyses, some of the suggestively associated SNPs in Stage 1 have been studied previously in various neuropsychiatric disorders as well as schizophrenia. Since an association between rs1800955 (-521CT) of DRD4 and schizophrenia was first reported by Okuyama et al (1999), this polymorphism has become one of the most intensively studied SNPs of DRD4 not only for schizophrenia (Mitsuyasu et al, 2001;Jonsson et al, 2003;Xing et al, 2007), but also for other psychiatric illness such as personality disorders (Okuyama et al, 2000;Mitsuyasu et al, 2001;Joyce et al, 2003) and ADHD (Kirley et al, 2004;Bellgrove et al, 2005;Yang et al, 2008). Overall, results are still inconsistent despite extensive investigations, and recent meta-analyses for associations between the SNP and schizophrenia showed significant effects with odds ratios of 1.15 to 1.22 (Jonsson et al, 2003;Allen et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with the Ser311Cys polymorphism, the fourth polymorphism of the gene, specifically the Ser/Ser genotype, were prone to respond to Risperidone treatment in a study with 123 Chinese participants [49] and demonstrated a decrease in cAMP synthesis inhibition in a study with 50 Japanese participants [50]. For the A-241G polymorphism, Asian individuals with A allele or A/A genotype showed a positive improvement to Risperidone treatment in a study with 125 Chinese participants [51] and in study with 120 Japanese participants [30]. However, American individuals with the A allele or A/A genotype showed a delayed response to Risperidone treatment in a study with 61 Caucasian and African American participants [44].…”
Section: Drd2mentioning
confidence: 99%
“…[5][6][7][8][9][10] A total of 127 unrelated schizophrenia patients (45 males and 84 females; mean±SD age: 36.1±11.1 years) were recruited from the Shanghai Mental Health Center on the basis of the following inclusion criteria: (1) had no physical complications or other psychiatric disorders; (2) had no history suggesting that antipsychotic treatment would be ineffective; (3) satisfied the DSM-IV criteria for schizophrenia; and (4) had not received any medication for 4-6 weeks before this study. All subjects gave signed, written informed consent through their responsible relatives before the study.…”
Section: Clinical Samplementioning
confidence: 99%
“…3,4 Genetic factors are commonly considered to be the main cause of these interindividual differences. [5][6][7][8][9][10] Previous studies have demonstrated that the expression levels of the human brain-derived neurotrophic factor (BDNF) gene in the prefrontal cortex, hippocampus are decreased in schizophrenic patients. 11 Clinical psychopharmacological and animal model-based experiments have also shown that antipsychotics can regulate the expression of BDNF.…”
Section: Introductionmentioning
confidence: 99%